1985
DOI: 10.1055/s-2007-1004371
|View full text |Cite
|
Sign up to set email alerts
|

A Primate Model (Macaca Mulatta) to Study the Pharmacokinetics of Heparin and Its Fractions

Abstract: We have extensively studied the hemostatic parameters and the responses to the anticoagulant action of heparin and its fractions in the primate model (M. mulatta) and found these to be identical to those obtained in humans. The functional properties of antithrombin III, alpha 2-antiplasmin, and platelet factor 4 were also identical to humans in amidolytic and coagulant assays. Human antibodies against FPA, B beta 15-42 peptide, platelet factor 4, and thromboxane B2 reacted with the primate antigen, and assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…These studies were conducted in an estab lished primate model [9], In the intravenous studies, the relative bioavailability of the anti-Xa effects were similar in all of the LMWHs except for the Novo LMWH and heparin. Wider variations in the anti-IIa ac tions were noted after a 50 IU/kg of the var ious LMWHs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were conducted in an estab lished primate model [9], In the intravenous studies, the relative bioavailability of the anti-Xa effects were similar in all of the LMWHs except for the Novo LMWH and heparin. Wider variations in the anti-IIa ac tions were noted after a 50 IU/kg of the var ious LMWHs.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative bioavailabil ity spectrum of each of the potency-activated lieparins was evaluated in the partial thromboplastine time, anti-Xa, Alla and Heptest. assays in a primate model in both the intravenous and subcutaneous route [9]. Bleeding studies were performed in a mod ified rabbit ear bleeding time model as reported pre viously [4], Protamine titration studies were con ducted in vitro by supplementing 10 pg/ml of prot amine to 1.0 IU/ml of each of the LMWHs and the anti-Xa activity was measured prior to and after the addition of protamine using the aca® (Du Pont; Wil mington, Del.)…”
Section: Methodsmentioning
confidence: 99%
“…The bioavailability of each agent was studied in a primate model of pharmacokinetics/pharmacodynamics as previously developed in our laboratory [3]. Bioavailability was measured in terms of Heptest®, antifactor Xa and antifactor Ila actions.…”
Section: Agents and Proceduresmentioning
confidence: 99%
“…The ratio between this different dynamic effects changes with time after a single administration and is de pendent on the route of drug delivery (intra venous, subcutaneous, intraperitoneal) [15]; moreover, this ratio changes when different doses are employed [16], This suggests that, even though the kinetics of LMWHs is li near, as previously demonstrated, their var ious components and/or the related dynamic effects might depend on saturable pro cesses.…”
mentioning
confidence: 93%
“…The presence of this active process of heparin biodegradation might account for the systematic differenes that may be demonstrated when compar ing the antithrombotic activities of equal amounts of heparin in vitro and in vivo [9]; the higher in vivo activity of heparin in fact might be explained by the transformation to which Heparin is subjected. The higher bio availability of LMWHs after subcutaneous adminstration with respect to intravenous administration might also be explained by a similar process [16], All experimental evidences suggest that no simple model may be used to describe the pharmacokinetics of heparin and LMWHs; only a complex model including a central pooling compartment where the heparin is stored and transformed might explain the various peculiarities of heparin kinetics [23] that are still uncompletely understood be cause of serious methodological shortcom ings, such as those resulting from the fre quent use of indirect measures of heparin concentrations.…”
mentioning
confidence: 99%